2010
DOI: 10.1515/jpm.2010.007
|View full text |Cite
|
Sign up to set email alerts
|

Women's attitudes to and perceptions of oral health and dental care during pregnancy

Abstract: Aims: To assess pregnant women's opinions on and perceptions of oral health and their relationship to oral hygiene and dental care practices. Methods: Questionnaire survey on perceived oral health, oral hygiene and utilization of dental services among 649 nulliparae attending for antenatal care at all public antenatal clinics in Adelaide, South Australia. Results: Women rated their general health significantly better than their oral health (P-0.001) and attributed more importance to healthy teeth for their bab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
95
4
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 43 publications
11
95
4
11
Order By: Relevance
“…Estos valores son similares a los reportados por Córdova & Bulnes que estiman un 66% y Rodríguez que refiere un 60% para la misma categoría. Estos valores establecen que no existe una relación significativa entre el conocimiento de salud oral y el nivel educacional de la madre, ya que como se puede ver en los resultados la diferencia es estadísticamente significativa (p<0,05 y IC95%) pero no clínicamente, ya que el mayor nivel educacional aumentaría solo 1 punto de conocimiento, como se observa en la RLM, lo que no nos habla de un nivel de conocimiento mayor (Almarales & Llerandi;Keirse & Plutzer, 2010). Para las otras variables es posible ver que a pesar que existe una tendencia de mayor conocimiento de salud oral a medida que es mayor la paridad y la edad, el aumento no es significativo en la RLM.…”
Section: Discussionunclassified
“…Estos valores son similares a los reportados por Córdova & Bulnes que estiman un 66% y Rodríguez que refiere un 60% para la misma categoría. Estos valores establecen que no existe una relación significativa entre el conocimiento de salud oral y el nivel educacional de la madre, ya que como se puede ver en los resultados la diferencia es estadísticamente significativa (p<0,05 y IC95%) pero no clínicamente, ya que el mayor nivel educacional aumentaría solo 1 punto de conocimiento, como se observa en la RLM, lo que no nos habla de un nivel de conocimiento mayor (Almarales & Llerandi;Keirse & Plutzer, 2010). Para las otras variables es posible ver que a pesar que existe una tendencia de mayor conocimiento de salud oral a medida que es mayor la paridad y la edad, el aumento no es significativo en la RLM.…”
Section: Discussionunclassified
“…In their study, Capasso et al showed that knowledge about dental problems during pregnancy is insufficient (12). According to Keirse et al study, only 28% of the pregnant women reported "very good" oral health (13). As stated by Wandera et al, George et al and Boggess et al it is essential to improve oral health during pregnancy (14-16).…”
Section: Introductionmentioning
confidence: 96%
“…She is the reference in the transmission of habits, customs and health practices [10,25]. t is of utmost importance to include the data of the mother in the child's treatment, since it is a reference to the child in health matters [18,26]. The unfavorable maternal perception to the child's oral health should be considered as a risk indicator, since she realizes the real risks when they present themselves [27].…”
Section: Discussionmentioning
confidence: 99%